2006
DOI: 10.1061/(asce)0733-9445(2006)132:5(781)
|View full text |Cite
|
Sign up to set email alerts
|

Improving Full-Scale Transmission Tower Design through Topology and Shape Optimization

Abstract: Application of structural optimization to transmission tower design is facilitated since major costs, e.g. material, transportation, erection and maintenance, are directly proportional to structural mass and economies of scale exist. In this paper, Structural Topology and Shape Annealing (STSA), a structural topology optimization method that combines structural grammars with simulated annealing, is applied to reduce the structural mass of an existing tower. STSA has previously been validated on smaller scale b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…The performance-based structural synthesis research has exhibited that shape annealing (Cagan and Mitchell, 1993) incorporating shape grammar and simulated annealing is sufficient to generate and realize innovative planar truss , dome , and cantilever spatial truss beam (Shea and Zhao, 2004). In addition, a recently published shape annealing study on planar truss structure identified such method as an optimizing tool to design a full-scale transmission tower (Shea and Smith, 2006). These insights establish a compelling rationale to target the computational generation for general spatial truss structures.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The performance-based structural synthesis research has exhibited that shape annealing (Cagan and Mitchell, 1993) incorporating shape grammar and simulated annealing is sufficient to generate and realize innovative planar truss , dome , and cantilever spatial truss beam (Shea and Zhao, 2004). In addition, a recently published shape annealing study on planar truss structure identified such method as an optimizing tool to design a full-scale transmission tower (Shea and Smith, 2006). These insights establish a compelling rationale to target the computational generation for general spatial truss structures.…”
Section: Introductionmentioning
confidence: 93%
“…Introduction of STSA for truss generation (Shea and Smith, 2006). Shape annealing was first applied to produce optimally directed shapes using the language specified by shape grammar (Cagan and Mitchell, 1993).…”
Section: Shape Annealing Algorithm For Truss Generationmentioning
confidence: 99%
“…As computational power increased, so did the scope of the applications. Structures such as bridges [10], electricity pylons [11], and even whole buildings [12] have been optimised using EC. A list of applications is covered extensively in the literature of Kicinger [4].…”
Section: Evolutionary Structural Designmentioning
confidence: 99%
“…Topology optimization offers a systematic search capability of the design space, which allows arriving at revolutionary designs in a variety of engineering applications, especially at the early stages of design conceptualization (Bendsoe and Sigmund 2004). Topology optimization is also increasingly being adopted as a design tool in structural engineering to develop high-performance structural layouts (e.g., Liang et al 2000; Swan and Rahmatalla 2001; Shea and Smith 2006; Gaynor et al 2012;Beghini et al 2014). Structural topology optimization combines mathematical optimization with finite-element analysis to search for optimized member connectivity and sizing under known applied loads and boundary conditions.…”
Section: Introductionmentioning
confidence: 99%